Application of binomials in English and Persian - Guilani, Mohammad Abdollahi; Tan, Kim Hua (Penerbit Universiti Kebangsaan Malaysia, 2017)
Binomials or word pairs can present themselves differently in languages and cultures and this may result in difficulty in learning and teaching a foreign language. Binomials are formed both linguistically and non-linguistically. A thorough study indicates there are many factors involved in the ordering of words in a pair. The ordering preferences can range from the frequency of words, to semantic features, and to phonological principles. In addition, the significant role of gender should not be downplayed in arranging the components of a binomial. This study has taken advantage of a self-designed questionnaire to support the findings. The participants, aged 18-20, included 179 Iranian i.e. 95 male and 84 female undergraduate students who were asked to read a short paragraph about a couple and choose names not only for the couple but also for their siblings and children. In addition, in some cases, the respondents had to write names for some characters in the made-up story and determine what type of responsibility the children of the family should take up. The results of the study indicated that in addition to the phonological rules which greatly contributed to the precedency of a certain word in a nominal pair, there were other factors that could determine which element should stand first. These parameters are further discussed in the article. The findings of this research can target language teachers in general and English-Persian language teachers/learners in particular. Curriculum designers and lexicographers can also benefit from the findings when designing course materials and writing dictionaries, respectively.